Strategies for Biomaterial-Based Spinal Cord Injury Repair via the TLR4-NF-κB Signaling Pathway - Lv, Bin; Shen, Naiting; Cheng, Zhangrong; Chen, Yuhang; Ding, Hua; Yuan, Jishan; Zhao, Kangchen; Zhang, Yukun (Frontiers in Bioengineering and Biotechnology, 2022)
The repair and motor functional recovery after spinal cord injury (SCI) has remained a clinical challenge. Injury-induced gliosis and inflammation lead to a physical barrier and an extremely inhibitory microenvironment, which in turn hinders the recovery of SCI. TLR4-NF-κB is a classic implant-related innate immunomodulation signaling pathway and part of numerous biomaterial-based treatment strategies for SCI. Numerous experimental studies have demonstrated that the regulation of TLR4-NF-κB signaling pathway plays an important role in the alleviation of inflammatory responses, the modulation of autophagy, apoptosis and ferroptosis, and the enhancement of anti-oxidative effect post-SCI. An increasing number of novel biomaterials have been fabricated as scaffolds and carriers, loaded with phytochemicals and drugs, to inhibit the progression of SCI through regulation of TLR4-NF-κB. This review summarizes the empirical strategies for the recovery after SCI through individual or composite biomaterials that mediate the TLR4-NF-κB signaling pathway.